Artificial Intelligence for Intrusion Detection Systems - Swarnkar M.; Rajput S.S. (My University, 2025)
This book is associated with the cybersecurity issues and provides a wide view of the novel cyber attacks and the defense mechanisms, especially AI-based Intrusion Detection Systems (IDS). Features: • A systematic overview of the state-of-the-art IDS • Proper explanation of novel cyber attacks which are much different from classical cyber attacks • Proper and in-depth discussion of AI in the field of cybersecurity • Introduction to design and architecture of novel AI-based IDS with a trans- parent view of real-time implementations • Covers a wide variety of AI-based cyber defense mechanisms, especially in the field of network-based attacks, IoT-based attacks, multimedia attacks, and blockchain attacks. This book serves as a reference book for scientific investigators who need to analyze IDS, as well as researchers developing methodologies in this field. It may also be used as a textbook for a graduate-level course on information security. © 2024 selection and editorial matter, Mayank Swarnkar and Shyam Singh Rajput; individual chapters, the contributors.